Mohamed Al-Fateh clinches Tokoh Siswa UMP 2019 title - UMP, PNC (2020)
Mohamed Al-Fateh Ab Razak, 22, was conferred the Tokoh Siswa UMP 2019 title for winning Leadership Award and Public Speaking Award at the Award Ceremony for Co-Curriculum & Student Recognition 2019 at Vistana Hotel Kuantan on 19 December 2019. Muar-born Mohamed Al-Fateh, who is pursuing the Bachelor of Computer Science (Software Engineering) course, was announced as the winner for his excellence display as the Chairman of Communication and Corporate Department under the Student Representative Council 2018/2019.